Investigação do potencial de absorção acústica de compósitos de argamassa com materiais reciclados - Flach, Fernanda (Universidade do Vale do Rio dos Sinos, 2012)
Production the activities of, maintenance and operation of the built environment are related to approximately half of the requirements for extraction and production of materials as well as similar proportion of raw waste generated by society. The construction industry is changes experiencing some paradigms, with the inclusion of performance requirements in the design process. One of them is the acoustical comfort. The objective of this study is to investigate the potential of acoustic insulation composites of mortar with replacement of sand for a few residues: agro-industry (rice husk), shoe industry (shoes’ foothills) and construction (forms of plywood). It was investigated some residues taxes (0%, 5%, 10%, 25%, 50%). The measurement of the acoustic absorption was carried out through the method using an impedance tube with sample size of Ø100mm. The results show that the compounds with the addition of wastes have higher sound absorption coefficients than the test was the best references, increasing the absorption capacity of these compounds. The rice husk was the best among the residuals, followed by the plywood waste and by of shoes’ foothills. Since there is no cost for incorporation of these residues, it can be concluded that the objectives have been achieved and that this study has contributed to improving the acoustic comfort and for the reduction of the impact of residues on the environment.
Keywords: Construção civil; Resíduos; Conforto acústico; Tubo de impedância; Construction; Waste; Acoustic comfort; Tube impedance; ACCNPQ::Engenharias::Engenharia Civil